All scars: towards a colonial phenomenology in Frantz Fanon - Gandarilla Salgado, José; Ortega Reyna, Jaime (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2017)
This text focuses on contemporary coordinates of discussion about Frantz Fanon´s work. Starting from the identification of two moments, in which different topics are discussed, we proceed to establish the standpoints to construct a "phenomenology of the colonial". This implies a process of approaching to recurrent phenomenologies in western thought. Subsequently, we proceed to draw lines of demarcation from the colonial element, present clearly in the work of Fanon, Black skin, white masks.